PERCEIVED INSUFFICIENT MILK (PIM) AMONG MOTHERS OF 0-6 MONTHS INFANTS IN CIPAYUNG HEALTH CENTRE, DEPOK INDONESIA: A QUALITATIVE STUDY - Bakara, Stella Maris; Fikawati, Sandra (Proceedings of the International Conference on Applied Science and Health, 2018)
Background: Exclusive breastfeeding is breast milk given to infant since their birth to the age of 6 (six) months, without adding and/or replacing with other foods or beverages (except medicines, vitamins, and minerals). One of the factors that affect the exclusive breastfeeding was the perceptions of insufficient milk. Milk insufficiency is considered to happen when the mother stops breastfeeding exclusively with some reasons such as no breast milk, low milk supply, or insufficient milk. This research was to examine more deeply the perception of insufficient milk and factor influencing it. Methods: This was a qualitative study that used a primary data of study